OVERVIEW OF COVID-19 CASES IN PREGNANCY AT THE HOSPITAL UNIVERSITAS SUMATERA UTARA, INDONESIA, WHEN THE PANDEMIC STORM HIT IN THE 2020-2022 PERIOD. : COVID-19 Cases In Pregnancy - Siregar, Muhammad Ernesto Azguevara Ganis; Siregar, Henry Salim; Lubis, Muara Panusunan; Adenin, Ichwanul; Lumbanraja, Irwin Lamtota (African Journal of Infectious Diseases (AJID), 2023)
Background: COVID-19 (Coronavirus 2019) is caused by SARS-CoV-2 (Severe Acute Respiratory Syndrome-Coronavirus-2), an acute infectious disease primarily affecting the respiratory system. Data on COVID-19 exposure during pregnancy and issues associated with COVID-19 during pregnancy remain limited. This research aimed to determine the number of pregnant women infected by COVID-19, laboratory test findings of pregnant women related to COVID-19 infection, infant outcome from mother with or without COVID-19 infection and referential status for COVID-19 and non-COVID-19 pregnant women at the USU Hospital during the 2020–2022 period. Materials and Methods: This research was conducted using a descriptive method with a cross-sectional study approach using a non-probability sampling technique by collecting secondary data from COVID-19 and non-COVID-19 pregnant women at the USU Hospital during the 2020-2022 period, where 112 samples were obtained. Results: The majority of COVID-19 pregnant women and non-COVID-19 pregnant women have been identified sequentially based on Hb (11.6%-decreased vs 79.5%-normal); Ht (11.6%-decreased vs 76.8%-increased); leukocytes (11.6%-increased vs 83%-normal); thrombocytes (8.9%-normal vs 86.6%-normal); PT (9.8%-normal vs 50.9%-normal); APTT (11.6%-normal vs 87.5%-normal); D-dimer (11.6%-long vs 56.3%-long); procalcitonin (7.1%-increased vs 87.5%-normal); NLR (8%-increased vs 82.1%-normal); CRP (12.5%-increased vs 87.5%-normal) and all of the baby outcomes were non-COVID-19 and the majority of pregnant women were not referred. Conclusion: Based on the data in this study, the majority of pregnant women and babies at the USU Hospital during the 2020–2022 period were non-COVID-19 positive and with non-referral status. Laboratory findings of COVID-19 in pregnancy significantly reveals abnormalities.